Analisis Pilihan Media Quizizz Dan TTS Sebagai Bentuk Media Pembelajaran Berbasis Teknologi Yang Memotivasi Taruna Teknika Pada Perkuliahan Fisika Terapan - Lusiani (Universitas Pahlawan Tuanku Tambusai, 2024)
The development of technology makes learning media one of the things that can be developed so that students are more motivated in learning. Learning media packaged in educational games is one alternative that can be done. There are several learning media in the form of educational games, namely Quizizz and Crossword Puzzles (TTS). The aim of this study is to analyze the choice of Quizizz and TTS media as a form of technology-based learning media that motivates engineering cadets in applied physics lectures. The data analysis method in this research is using descriptive content analysis study. Data collection techniques use questionnaires and literature studies. It was concluded that the percentage in first place, namely the choice of the Quizizz application, was worth 82.9%. Meanwhile, in second place, the choice of TTS application was worth 26.8% as a form of technology-based learning media that motivates engineering cadets in applied physics lectures.